Fixation of multifragmentary patella fractures using a bilateral fixed-angle plate - Thelen, Simon; Schneppendahl, Johannes; Grassmann, Jan; Hakimi, Mohssen; Eichler, Christian; Windolf, Joachim; Wild, Michael; Betsch, Marcel (Orthopedics, 2013)
This biomechanical study is the first to compare 3 fixation methods - bilateral fixedangle plate, modified anterior tension wiring, and cannulated lag screws with anterior tension wiring - in multifragmentary distal patella fractures. A T-shaped 3-part fracture simulating a multifragmentary articular distal patella fracture (AO/OTA 34-C2.2) was created in 18 human cadaver knee specimens. Three groups were created using homogenous ages and bone mineral densities based on the fixation method received. Repetitive testing over 100 cycles was performed by moving the knee against gravity from 90° flexion to full extension. Failure was defined as fracture displacement greater than 2 mm. In all patellae using fixed-angle plates, an anatomical fracture reduction could be maintained throughout cyclic testing, whereas anterior tension wiring and lag screws with tension wiring showed significant fracture displacement after 100 cycles, with mean fracture gaps of 2.0±1.3 and 1.9±1.6 mm, respectively. The differences in fracture gaps between the fixed-angle plate group and the other 2 groups were statistically significant. In both groups using tension wiring, half of the constructs (3 of 6 in each group) failed due to a fracture displacement greater than 2 mm. The bilateral fixed-angle plate was the only fixation method that sustainably stabilized a multifragmentary articular distal patella fracture during cyclic loading when compared with modified anterior tension wiring and cannulated lag screws with anterior tension wiring. (Figure Presented).
CRIS-Team Scopus Importer:2022-07-20